HUBUNGAN PERAN PATUGAS DAN PENGALAMAN KB DENGAN PERGANTIAN METODE KB DI KECAMATAN TEMBALANG KOTA SEMARANG TRIWULAN II TAHUN 2016 - Okta Nidya Boro Samosir; Dharminto Dharminto; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2016)
In Jawa Tengah, 2015 there are 48.541 acceptors who have changed their FP method. Most of them subtitute to injectable FP method. In Semarang, there are 1.333 acceptors have changed their FP method, most of them substitute to injectable FP method. In District Tembalang recorded 75 acceptors have changed its method of family planning from the period 2013-2015. Preliminary study on the 10 acceptors turnover of family planning methods known that 7 of them substitute FP methods from  LTM to non-LTM with the biggest reason is because of side effects which is menstrual disordes (100%), change in body weight (80%), bleeding disorder (40%), and whitish (20%). The purpose of this study is to analyze the role of family planning officers and planning experience with the change of family planning methods in District Tembalang, Semarang. This type of research is explanatory research with cross sectional study design. The population in this study are all acceptors turnover family planning methods are recorded in primary health centers Rowosari and Kedungmundu and the sample is total population of 56 people. Analysis of the data used univariate analysis with frequency distribution and bivariate analysis using Chi Square test with significancy level (α) of 5%. The results showed that the largest percentage of the lack of family planning officer role (51.8%), there are experiences KB themselves (69.6%), and there are not experience of others (80.4%). The results of analysis of Chi Square, there is no relationship role for FP officer with the replacement of family planning methods (p value: 0.636), there is no relationship experiences FP others with the replacement of family planning methods (p value: 0,761). It is advisable for family planning officials to explain about family planning methods with more deeply.